Factors associated with health-risk perception of heat waves among agroecological and conventional farmers in the tropics - How, Vivien; Singh, Shyamli; Dang, Thinh; Guo, How-Ran (Common Ground Research Networks, 2021)
Given that Asian countries rely on agriculture for livelihoods, it is necessary to understand the background of both agroecological and conventional farmers’ perceptions of extreme temperature effects on health and assess the differences in their risk perceptions. By comparing both farming communities, this study showed that sociodemographic characteristics, agricultural activities, and experiences with heat waves influence farmers’ perceptions differently and underscore the likelihood, severity, and worry about the risk of heat waves. Instead of focusing on climate risks, this study suggests that health risks should be included as part of public communication to enhance climate change mitigation and adaptation strategies.